Impact of Optimizing the Emergency Care Process on the Emergency Effect and Prognosis of Patients with Hepatic Encephalopathy - Fang Wei; Haihong Tan; Yubiao He; Xin Shu (Emergency Medicine International)
Hepatic encephalopathy (HE) is a serious complication caused by liver disease and is one of the leading causes of death in patients. Studies have shown that proper emergency care for patients after the occurrence of HE can improve their prognosis and quality of life. Therefore, this study focuses on the effect of optimizing the emergency care process on the effectiveness and prognosis of emergency care for patients with hepatic encephalopathy. In this study, we set 32 patients with HE admitted to receive routine emergency care between May 2020 and March 2021 as the control group and 34 patients with HE admitted to receive optimized emergency care processes between April 2021 and February 2022 as the observation group. The satisfaction of patients’ families with this care was assessed using a self-administered nursing satisfaction questionnaire to record the outcome of emergency care, quality of care, and prognosis of patients in the two groups of palliative care. The data collected were analyzed using SPSS17.0 software, and the results showed that the time spent on diagnosis, resuscitation, DTP, and DTT was much lower in the observation group than in the control group, and the scores related to the quality of care, such as ambulance technique, humanistic care, resuscitation efficiency, and resuscitation effect, were all higher than those of the control group, and the satisfaction of the family members in the observation group was also significantly higher than that of the control group (P<0.05). The success rate of first aid in the observation group was 100.00%, which was higher than 93.72% in the control group, but the difference between the two groups was not significant (P>0.05). It can be seen that the application of an optimized emergency nursing process in HE patients is effective, which can effectively improve the success rate of HE resuscitation, shorten the resuscitation time and condition diagnosis, improve the resuscitation effect, improve the quality of nursing care, and improve the prognosis of patients to a certain extent.